2019
DOI: 10.1080/21691401.2019.1671433
|View full text |Cite
|
Sign up to set email alerts
|

Taraxasterol from Taraxacum prevents concanavalin A-induced acute hepatic injury in mice via modulating TLRs/NF-κB and Bax/Bc1-2 signalling pathways

Abstract: Immune hepatic injury is a liver disease closely related to an immune imbalance of T cells and macrophages. Our previous series of studies have demonstrated that taraxasterol isolated from Taraxacum possesses great anti-inflammatory and immunomodulatory effects in vivo and in vitro. In this study, we explored the preventive effects of taraxasterol and its underlying mechanisms on concanavalin A (Con A)-induced acute hepatic injury in mice. It was found that treatment with taraxasterol significantly decreased t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…Maybe there are other antiviral mechanisms. New evidences show that dandelion extracts improve immune responses [44,45].Taraxasterol possesses immunomodulatory effects to prevent acute hepatic injury [46]. The dysfunction of innate immune cells and adaptive immune cells is a critical factor, which leads to virus clearance failure [47].…”
Section: Discussionmentioning
confidence: 99%
“…Maybe there are other antiviral mechanisms. New evidences show that dandelion extracts improve immune responses [44,45].Taraxasterol possesses immunomodulatory effects to prevent acute hepatic injury [46]. The dysfunction of innate immune cells and adaptive immune cells is a critical factor, which leads to virus clearance failure [47].…”
Section: Discussionmentioning
confidence: 99%
“…Taraxasterol, resulted in a major downregulation in TLR2, TLR4, and NF-κB p65 expression and decreased the Bax/Bc1-2 expression ratio in hepatic tissues. Accordingly, taraxasterol prevented Con A-related liver damage by inhibition of the TLRs/NF-κB signaling pathway and promoting Bax/Bc1-2 anti-apoptotic signaling pathway [48].…”
Section: Terpenesmentioning
confidence: 91%
“…Previous studies found that Taraxacum officinale extract improves immunity, increasing nitric oxide (NO) and cytokines production in mice (Kim et al 1998;Lee et al 2012). Another study showed that taraxasterol can activate the Bax/Bc1-2 anti-apoptotic signalling pathway, which is downregulated in autoimmune disorders (Sang et al 2019). A study by Tan et al (2017) found that Taraxacum officinale extracts ameliorate the immune response in vivo (Table 1).…”
Section: Effects On the Immune Systemmentioning
confidence: 97%